DEVELOPMENT AND PSYCHOMETRIC PROPERTIES OF ADVERSE CHILDHOOD EXPERIENCES SCALE FOR ADOLESCENTS - Riaz, Maryam; Bano, Zaqia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To develop a scale and establish psychometric properties to measure Adverse Childhood Experiences of Adolescents in Urdu language.Study Design: Cross sectional analytical study.Place and Duration of Study: Department of Psychology, University of Gujrat, from Dec 2019 to Oct 2020.Methodology: After the approval of proposal initial item pool of 145 items was generated with the help of DSM-5, extensive literature review and focus group interviews (Girls=25, Boys=25). Expert evaluation shortens it into 137 items whereas pilot study retained 132 items for final administration. Data was obtained from 1331 adolescents with age range of 12-19 from educational institutions and community in district Gujrat. Exploratory Factor Analysis, Confirmatory Factor Analysis and reliability analysis were carried out to analyze the data.Results: Exploratory factor analysis explored 38 reliable items for Adverse Childhood Experiences scale under four sub factors; Sexual Abuse, Neglect, Physical Abuse, and Psychological Abuse whereas 12 items were confirmed for final scale through model fit (p-value=0.000, CFI=0.968, GFI=0.975, AGFI=0.959, RMSEA=0.049) of Confirmatory Factor Analysis.Conclusion: A scale to estimate Adverse Childhood Experiences of adolescents in Urdu language is competently developed and established with 12 questions and four sub-scales.